2001
DOI: 10.1007/bf03401959
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Interleukin-8 by Hypoxia in Human Macrophages—A Potential Role in the Pathogenesis of the Acute Respiratory Distress Syndrome (ARDS)

Abstract: Background: The acute respiratory distress syndrome (ARDS) represents a form of severe acute inflammatory lung disease. We have previously demonstrated significantly raised interleukin-8 (IL-8) levels in the lungs of atrisk patients that progress to ARDS, and identified the alveolar macrophage as an important source of this chemokine. We wished to extend this study in a welldefined group of patients with major trauma, and to investigate potential mechanisms for rapid intrapulmonary IL-8 generation. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 55 publications
4
75
1
1
Order By: Relevance
“…Although monocytes contribute to the development of atherosclerotic lesions, IL-8 is a powerful trigger for firm adhesion of monocytes to vascular endothelium (10). It has been shown that hypoxia induces expression and/or generation of IL-8 (13,30), indicating that OSAS-associated desaturation could lead to upregulatation of IL-8 expression. In addition, one could presume that the effective therapy for OSAS may attenuate hypoxic stress, which may prevent the development of vascular lesions via the reduction of IL-8 production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although monocytes contribute to the development of atherosclerotic lesions, IL-8 is a powerful trigger for firm adhesion of monocytes to vascular endothelium (10). It has been shown that hypoxia induces expression and/or generation of IL-8 (13,30), indicating that OSAS-associated desaturation could lead to upregulatation of IL-8 expression. In addition, one could presume that the effective therapy for OSAS may attenuate hypoxic stress, which may prevent the development of vascular lesions via the reduction of IL-8 production.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic stress increases the adherence of neutrophils to endothelial cells, and this increased adherence is mediated by proinflammatory mediators, including ICAM-1 (2) and IL-8 (13,30). Furthermore, it has been reported that hypoxia induces the synthesis and expression of both ICAM-1 and IL-8 via the activation of nuclear transcription factor (NF)-B (7,36,37).…”
mentioning
confidence: 99%
“…42 The formation of MCP-1 is reduced by hypoxia in ovarian cancer cells, 43 macrophages 44,45 and human synovial fibroblasts. 46 However, hypoxia upregulated MCP-1 formation in cultured neonatal mouse cardiac myocytes and MCP-1 decreased hypoxia-induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL8 protein is upregulated in human MDM within 2 hr of exposure to hypoxia, via a mechanism involving the transcription factors AP-1 and C/EBP but not NFjB or HIF. 80 Furthermore, primary murine macrophages respond to hypoxia by secreting elevated levels of MIP-2 (murine CXCL1) via an NFjB-mediated mechanism. 61 These CXC chemokines have been shown to stimulate endothelial and tumor cell proliferation and migration in vitro, and revascularization in vivo and have been implicated in mediating nonsmall-cell lung tumor-associated angiogenesis.…”
Section: Tam Gene Expression In Response To Tumor Hypoxiamentioning
confidence: 99%